PARTICIPATORY RIGHTS OF VICTIMS OF CRIME: WITH SPECIAL REFERENCE TO INDIAN POSITION (International Journal of Food and Nutritional Sciences, 2022)
The criminal Justice system has its objective to protect triangulation of interests- ie rightsof accused, victim and Public at large. However in India, till recently one dimensional approachwas adopted concentrating more on rights of the accused vis –a –vis State and victim was aforgotten party in criminal justice system